Give Me the Room to Learn: Associations Between Job Control and Work-Related Learning - Weststar, Johanna (Just Labour, 2007)
Societal rhetoric claims that the intellectual capital of workplaces must be leveraged if Canada is to compete in the "knowledge economy". To achieve this, however, employers must create work environments that are favorable to workers and conducive to learning. This paper uses a sample of 5800 Canadian workers from the Work and Lifelong Learning Survey and twenty interviews with Information Technology workers from the Education-Job Requirement Matching Project to focus on the relationship between worker control and learning engagement. The data show that increased levels of social and technical control are associated with increased worker engagement in formal courses, informal education (mentoring) and non-taught learning. This research has implications for job design that includes real and meaningful opportunities for worker input and agency into their own tasks and broader organizational decision-making. These results provide important information for future research regarding the inclusion and conceptualization of learning and job control constructs.